The Effect of DG Placement on Vulnerability Assessment of ADNs - Pourramezani, Kiarash; Baghaee, Hamid Reza; Gharehpetian, Gevork B. (2025 10th International Conference on Technology and Energy Management (ICTEM), 2025)
Nowadays, distribution networks (DNs) are often subject to discuption. Thus, vulnerability assessment (VA) becomes crucial. VA uses a set of criteria to determine the best cases of distribution generation (DG) placement in active distribution networks (ADNs) that have the highest stability based on vulnerability indicators while adhering to the network's operational constraints. Given the critical role of telecommunication networks in microgrids (MGs), as they enable control and data exchange to monitor and maintain stability, these networks are inherently vulnerable to cyber threats. However, this study is based on the optimal conditions foreseen for cyber threats. This research examines the vulnerability and stability of the network from the perspective of the appropriate location of DGs. The test network is the same 33-bus IEEE network. All tens of thousands of possible scenarios of three DG placements in this network are examined by the search vector artificial physics optimization (SVAPO) algorithm. The best case is selected and analyzed.